Sex Differences in Epicardial Adipose Tissue: Association With Atrial Fibrillation Ablation Outcomes - Zhu, Jing; Zhuo, Kaimin; Zhang, Bo; Xie, Zhen; Li, Wenjia (Frontiers in Cardiovascular Medicine, 2022)
Background: There are significant differences in the prevalence and prognosis of atrial fibrillation (AF) between sexes. Epicardial adipose tissue (EAT) has been found as a risk factor for AF. This study aimed to evaluate whether sex-based EAT difference was correlated with AF recurrence and major adverse cardiovascular events (MACE). Methods: In this study, postmenopausal females and age, BMI, and type of AF matched males who had received first catheter ablation were included. EAT volume was quantified based on the pre-ablation cardiac computed tomography (CT) images. Clinical, CT and echocardiographic variables were compared by sex groups. The predictors of AF recurrence and MACE were determined through Cox proportional hazards regression. Results: Females were found with significantly lower total EAT volumes (P<0.001) but higher periatrial/total (P/T) EAT ratios (P=0.009). The median follow-up duration was 444.5 days. As revealed by the result of the Kaplan-Meier survival analysis, the females were found with a significantly higher prevalence of AF recurrence (log rank, P=0.011) but comparable MACE (log rank, P=0.507) than males. Multivariate analysis demonstrated that females (HR, 1.88 [95% CI, 1.03, 4.15], P=0.032), persistent AF (HR, 2.46 [95% CI, 1.19, 5.05], P=0.015), left atrial (LA) dimension (HR, 1.47 [95% CI, 1.02, 2.13], P=0.041) and P/T EAT ratio (HR, 1.73 [95% CI, 1.12, 2.67], P=0.013) were found as the independent predictors of AF recurrence, Sex-based subgroup multivariable analysis showed that P/T EAT ratio was an independent predictor of AF recurrence in both males (HR, 1.13 [95% CI, 1.01, 1.46], P=0.047) and females (HR, 1.37 [95% CI, 1.11, 1.67], P=0.028). While age (HR, 1.81 [95% CI, 1.18, 2.77], P=0.007), BMI (HR, 1.44 [95% CI, 1.02, 2.03], P=0.038) and periatrial EAT volume (HR, 1.31 [95% CI, 1.01, 1.91], P=0.046) were found to be independent of MACE. Conclusions: Females had higher P/T EAT ratio and AF post-ablation recurrence but similar MACE, as compared with males. Females and P/T EAT ratio were independent determinants of AF recurrence, whereas age and periatrial EAT volume were found as independent predictors of MACE.